Pembenahan Tata Kelola Situs Istana Sisingamangaraja Di Kabupaten Humbang Hasundutan Tahun 2023 - Risma Simanjuntak; Tio R.J. Nadeak; Robert J.T. Sitio; Yulia K.S. Sitepu; Maringan Sinambela (Universitas Katolik Widya Karya Malang, 2023)
This research aims to find out the governance exists at the Sisingamangaraja Palace and the efforts to improve the management of the Sisingamangaraja Palace in Humbang Hasundutan Regency. This research uses a qualitative research method with a descriptive approach with an emphasis on the natural environment (naturalistic setting) on the economy, culture, religion, environment, political conditions which will be told in detail and the data comes from primary and secondary data. With data collection techniques through observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. As for the results; from this research is that the governance at the Sisingamangaraja Palace is as follows: 1). Cleanliness of Sisingamangaraja Palace; 2). Manufacturing of hygiene and maintenance boxes; 3). Providing accommodation; 4). Procurement of guides; and 5). Provide facilities. Efforts made to improve the management of the Sisingamangaraja Palace include planning the management of the Sisingamangaraja Palace, organizing the management of the Sisingamangaraja Palace, implementing the management of the Sisingamangaraja Palace, and supervising the management of the Sisingamangaraja Palace